Assessing the synergy between a seawater pumping system for mining facilities and the cooling system of a CSP plant in Northern Chile. (20th April 2022) - Gacitúa, Jorge A.; Palma-Behnke, Rodrigo; Cardemil, José M.; Cerda, María Teresa; Godoy, Felipe; Dinter, Frank
Abstract: The Atacama Desert presents the highest Direct Normal Irradiance (DNI) levels on the planet and at the same time is one of its driest places on Earth. The region concentrates a large number of copper mining facilities and is currently considered as a hotspot for the deployment of solar technologies. The mining activity consumes large amounts of water in its processes, and for driving such processes several of the facilities consider seawater pumping systems. The present article describes a technical and economic evaluation of coupling the cooling system of a Concentrating Solar Power (CSP) plant and the seawater pipeline. The analysis considers a location in northern Chile and the operation of a CSP plant, which is assessed using a validated simulation tool. The base scenario considers evaporative cooling, which is compared to other cooling approaches such as: dry cooling, once through, and coupling a Multi Effect Distillation (MED) plant, where the last two consider a connection to the pumping pipeline. The energy production and the resulting economic benefit are evaluated for each cooling scenario. It is observed that the scenarios using seawater deliver more energy than the dry cooling scenario. The once-through and MED cases show the best economic performance in terms of the Net Present Value (NPV). The simulations carried out allowed to identify the synergistic performance between the mining pumping system and the operation of the CSP plant, enabling to exploit additional benefits from its integration.